Efeitos imediatos da plataforma vibratória no desempenho neuromuscular do quadríceps femoral, após reconstrução do LCA: ensaio controlado, randomizado e cego - Costa, Karinna Sonálya Aires da (2016)
Objective: to investigate the immediate effect of the vibrating platform on the neuromuscular performance of the quadriceps femoris and on the postural oscillation of subjects submitted to Anterior Cruciate Ligament (ACL) reconstruction. Materials and methods: this study is a randomized and blind clinical trial. Forty-four male volunteers (average age of 27,4 ±6,2 IMC of 26,85± 3,8 Kg/m² and post surgery timeframe of 17± 1,4 weeks) were randomized into two groups: OFF platform (n=22, protocol of exercise over the vibrating platform off) and ON platform (n=22 protocol of exercise over the vibrating platform on, 50Hz frequency and 4mm of amplitude). All volunteers were submitted to assessment the isokinetic evaluation of the quadriceps femoris (isometric and isokinetic at 60°/s) and of the electromyography activity of the muscles Vasto Lateralis (VL) and Vasto Medialis (VM), besides the postural oscillation (baropodometry) in two distinct moments: before and immediately after the intervention protocol. The data was analyzed through the SPSS 20.0 software, with a 5% significance level. To verify the homogeneity of the groups it was used an ANOVA one way, and a ANOVA mixed model to compare the intra and inter groups. Results: it was observed differences between the pre and the post, to latero lateral velocity, isometric torque peak and total work in comparison with intragroup. However, it wasn’t verified any difference in comparing the intergroup in the preevaluation and in the post-evaluation protocol over the vibrating platform. Conclusion: the use of the vibrating platform doesn’t change as an immediate manner the isokinetic performance of the quadriceps femoris, the electromyography activity of the VL and the VM, also doesn’t interfere with the postural oscillation of individuals that were submitted to the ACL reconstruction.